MODERN METHODS OF TEACHING MATHEMATICS IN PRIMARY GRADES - Salomov Abdinazar Abdivasikhovich (American Journals, 2025)
This article examines the use of modern methods in teaching mathematics in primary grades. Research shows that innovative approaches, interactive methods, and information and communication technologies (ICT) help develop students' logical thinking, analytical skills, and independent learning abilities.Effective use of interactive teaching methods, STEAM methodology, case studies, project-based learning, and information technology makes mathematics lessons more engaging and productive. Additionally, the article analyzes the advantages of modern methods and the challenges encountered in their practical implementation.
Keywords: Primary education, teaching mathematics, modern methods, interactive learning, information technology, STEAM, project-based learning, case study, differentiated approach, pedagogical innovations.